2018
DOI: 10.1002/kin.21179
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase rate coefficients for a series of alkyl cyclohexanes with OH radicals and Cl atoms

Abstract: The rate coefficients of the reactions of OH radicals and Cl atoms with three alkylcyclohexanes compounds, methylcyclohexane (MCH), trans-1,4-dimethylcyclohexane (DCH), and ethylcyclohexane (ECH) have been investigated at (293 ± 1) K and 1000 mbar of air using relative rate methods. A majority of the experiments were performed in the Highly Instrumented Reactor for Atmospheric Chemistry (HIRAC), a stainless steel chamber using in situ FTIR analysis and online gas chromatography with flame ionization detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…Consequently, the obtained temperature-dependent (283−363 K) rate coefficient for the reaction of MCH with a Cl atom is k(T) = [(4.48 ± 0.75) × 10 −11 ]exp[(604.42 ± 24.66)/T] cm 3 molecule −1 s −1 . The average rate coefficient for the reaction of MCH with a Cl atom at 298 K is (3.36 ± 0.34) × 10 −10 cm 3 molecule −1 s −1 , which is in excellent agreement with the reported rate coefficients of (3.47 ± 0.12) × 10 −10 , (3.51 ± 0.37) × 10 −10 , and (3.11 ± 0.16) × 10 −10 cm 3 molecule −1 s −1 by Aschmann et al, 18 Bejan et al, 19 and Ballesteros et al 17 respectively. Although the rate coefficients obtained for the reaction of MCH with Cl atoms relative to propylene appear to be consistently higher, they are well within the experimental uncertainties/error limits.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consequently, the obtained temperature-dependent (283−363 K) rate coefficient for the reaction of MCH with a Cl atom is k(T) = [(4.48 ± 0.75) × 10 −11 ]exp[(604.42 ± 24.66)/T] cm 3 molecule −1 s −1 . The average rate coefficient for the reaction of MCH with a Cl atom at 298 K is (3.36 ± 0.34) × 10 −10 cm 3 molecule −1 s −1 , which is in excellent agreement with the reported rate coefficients of (3.47 ± 0.12) × 10 −10 , (3.51 ± 0.37) × 10 −10 , and (3.11 ± 0.16) × 10 −10 cm 3 molecule −1 s −1 by Aschmann et al, 18 Bejan et al, 19 and Ballesteros et al 17 respectively. Although the rate coefficients obtained for the reaction of MCH with Cl atoms relative to propylene appear to be consistently higher, they are well within the experimental uncertainties/error limits.…”
Section: Resultssupporting
confidence: 92%
“…Aschmann et al 18 measured the rate coefficient using the RR method for the reaction of MCH with Cl atoms at 298 K and is reported to be (3.47 ± 0.12) × 10 −10 cm 3 molecule −1 s −1 . Bejan et al 19 reported the rate coefficient for the reaction of Cl atoms with MCH as k (MCH+Cl) = (3.45 ± 0.37) × 10 −10 cm 3 molecule −1 s −1 using the RR technique. Sprengnether et al 20 reported the rate coefficient for the reaction of OH radicals with MCH using the absolute technique at 298 K as k (MCH+OH) = (9.42 ± 0.12) × 10 −12 cm 3 molecule −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…20 The derived results have been incorporated in the JetSurF II mechanism. 15 The reactions of OH radical and Cl atom with a series of alkylcyclohexanes were also experimentally studied by Bejan et al 21 at 293 K. Besides the above experiments, few studies are performed on the elementary reactions related to MCH combustion to the best of our knowledge due to the limitations of experimental methods. On the other hand, ab initio chemical kinetics have become an important tool for accurate rate constant predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Begum et al 31 evaluated the total and site-specific rate constants for MCH+OH at 298 K and 1 atm by using quantum chemical calculations and the canonical transition state theory. For reactions between poly-alkyl substituted cycloalkanes and OH, only Bejan et al 29 and Ballesteros et al 28 reported the rate constants at room temperatures, involving D14MCH+OH at 293 and 298 K, and T135MCH+OH at 298 K. However, to the best of our knowledge, the site-specific kinetics over a wide temperature range regarding H-abstraction reactions for poly-alkyl sub-stituted cycloalkanes with OH have not been systematically explored yet, even for the most representative and the simplest dimethylcyclohexane isomers.…”
Section: Introductionmentioning
confidence: 99%
“…For the pentatomic-ring chemistry, Wu et al and Chen et al conducted the kinetics investigation for the reaction of cyclopentane (CPT) with OH, H, CH 3 , and C 2 H 5 radicals by the variational transition state theory and multidimensional tunneling approximation. In the case of MCH+OH, many room-temperature (293–298 K) measurements of the total rate constants were available by using various technologies including Fourier transform infrared (FTIR) spectrometer, GC-MS, and laser-induced fluorescence (LIF). Sprengnether et al and Bejan et al further measured the temperature-dependent rate constants for MCH+OH at 230–379 K and 273–343 K, respectively by using the relative rate method. Sivaramakrishnan and Michael conducted the total rate measurements of MCH+OH with the reflected shock tube over the range of 836–1273 K and evaluated the site-specific rate constants based on ab initio and transition states calculations.…”
Section: Introductionmentioning
confidence: 99%